Laparoscopic Fimbrioplasty and Neosalpingostomy in Female Infertility: A Review of 402 Cases at the Gynecological Endoscopic Surgery and Human Reproductive Teaching Hospital in Yaoundé-Cameroon - J Kasia; J Ngowa; Y Mimboe; M Toukam; A Ngassam; C Noa; E Belinga; A Medou (JRI, 2016)
Background: More than 70 million couples suffer from infertility worldwide. The aim of this study was to evaluate the fertility outcomes after laparoscopic fimbrioplasty and neosalpingostomy in female infertility. Methods: Laparoscopic distal tuboplasty was carried out for 402 cases at the Gynecological Endoscopic Surgery and Human Reproductive Teaching Hospital in Yaoundé-Cameroon in Central Africa from December 2002 to December 2007. Laparoscopic fimbrioplasty and neosalpingostomy were done using bipolar electrocoagulation and conventional endoscopic instruments. Log-rank test was used to compare cumulative rate curves of intrauterine pregnancy with respect to the tubal stages. P<0.05 was considered statistically significant. Results: The mean age of the patients was 31.6±5.45 years. Secondary infertility was the most frequent type of infertility (70.14%). The laparoscopic tubal surgery done consisted of fimbrioplasty in 185(46%) cases and neosalpingostomy in 217(54%) cases. Of 260 women followed up after tuboplasty, there were overall 74(28.48%) pregnancies; 68(26.1%) intrauterine pregnancies and 6(2.3%) ectopic pregnancies. Pregnancy rates were significantly associated to the tubal stage (63% in stage 1, 15% in stage 3 and 00% in stage 4; p<0.001) and the adnexal adhesion scores (73.91% in the absence of adnexal adhesions and 8.8% in the case of a severe adnexal adhesion score). Of the 68 intrauterine pregnancies, there were 60(88%) live births and 8(12%) spontaneous abortions. Conclusion: It is believed that laparoscopic fimbrioplasty and neosalpingostomy should be the preferred choice when faced with tubal distal occlusion in a context of female infertility. This implies that training in endoscopic surgery should be regarded as an important issue in developing countries.